Characterization of Palm Shell-Derived Bio-Oil Through Pyrolysis - Leila Utarina; Rusdianasari Rusdianasari; Leila Kalsum (Green Engineering Society, 2022)
Lignocellulosic biomass is a renewable resource used to produce energy, fuels, and chemicals. This study aimed to determine the effect of pyrolysis temperature on product yield and product characterization of bio-oil. In this study, palm shells were selected and prepared as raw materials for bio-oil production. Palm shells were first soaked in 10% HCl and then pyrolyzed at temperatures of 300 oC, 350 oC, 400 oC, and 450 oC in a fixed bed reactor. Afterward, the reactor will emit smoke which later will condense into bio-oil. The experimental results show that a temperature of 450 oC will be a better choice for higher bio-oil yields (44.59%). The characteristics of the bio-oil obtained are density (905 – 1015.17 kg/m3), Kinematic Viscosity (1.21 – 1.5 mm2/s), and flash point (60 – 68.7 oC).